Predictors of Altered Upper Extremity Function During the First Year After Breast Cancer Treatment. (September 2016) - Smoot, Betty; Paul, Steven M.; Aouizerat, Bradley E.; Dunn, Laura; Elboim, Charles; Schmidt, Brian; Hamolsky, Deborah; Levine, Jon D.; Abrams, Gary; Mastick, Judy; Topp, Kimberly; Miaskowski, Christine
ABSTRACT: Objective: The purpose of this study was to evaluate trajectories of and predictors for changes in upper extremity (UE) function in women (n = 396) during the first year after breast cancer treatment. Design: Prospective, longitudinal assessments of shoulder range of motion (ROM), grip strength, and perceived interference of function were performed before and for 1 year after surgery. Demographic, clinical, and treatment characteristics were evaluated as predictors of postoperative function. Results: Women had a mean (SD) age of 54.9 (11.6) years, and 64% were white. Small but statistically significant reductions in shoulder ROM were found on the affected side over 12 months ( P < 0.001). Predictors of interindividual differences in ROM at the 1-month assessment were ethnicity, neoadjuvant chemotherapy, type of surgery, axillary lymph node dissection, and preoperative ROM. Predictors of interindividual differences in changes over time in postoperative ROM were living alone, type of surgery, axillary lymph node dissection, and adjuvant chemotherapy. Declines in mean grip strength from before through 1 month after surgery were small and not clinically meaningful. Women with greater preoperative breast pain interference scores had higher postoperative interference scores at all postoperative assessments. Conclusion: Some of the modifiable risk factors identified in this study can be targeted for intervention to improve UE function in these women. Abstract : Supplemental digital content is available in the text.